Minimum quality standards and benchmarking in differentiated duopoly - Peter Michaelis; Thomas Ziesemer (The Japanese Economic Review, 2020)
We study a two-period model of a duopoly with goods differentiated by quality. The periods' length corresponds to the goods' useful lifespan, and consumers are heterogeneous in their valuation of quality. In the second period, the regulator fixes a minimum quality standard based either on the quality supplied by the high-quality firm in the first period (strict regulation) or on the average quality supplied in the first period (average regulation). Assuming a covered market, we show that such an approach leads to decreasing qualities in the first period, and increasing qualities in the second one. In both periods, net utility aggregated over consumers is increasing and profits aggregated over firms are decreasing. Taken together, average regulation always leads to an increase in the present value of welfare, whereas strict regulation can cause a decline. If the discount factor exceeds a certain threshold, a policy based on average regulation is even superior to implementing the optimal minimum quality standard already in the first period.
Keywords: C72; D43; I18; L15; 330; C72; D43; I18; L15